Effect of genetic background, pen size and outdoor access on meat quality in two slow growing broiler hybrids. (2nd January 2021) - Sampels, S.; Pickova, J.; Gatchell, S.; Karlsson, A.; Yngvesson, J.; Arvidsson Segerkvist, K.
ABSTRACT: The aim was to evaluate the effect of two different rearing systems, indoor small pens (S) and big pens with outdoor access (B), on meat quality and fatty acid (FA) composition of two slow growing broiler hybrids (Rowan Ranger [RR] and Hubbard CYJA57 [H]). In addition, changes in the phospholipid FA composition, due to the possibility of more movement, were investigated. The results regarding meat quality were exclusively influenced by genotype, where RR chickens had higher breast weight, higher Warner-Bratzler shear force and higher pH than H chickens. Differences in lipid composition were found both due to hybrid and to the rearing system. The H birds were slightly leaner and had, therefore, higher proportions of phospholipids. Rearing in a big pen resulted in lower concentrations of 16:0 and higher concentrations of both total n-3 and n-6 fatty acids and of individual long chain polyunsaturated FA.